CAR (CARSKNKDC) Peptide Modified ReNcell-Derived Extracellular Vesicles as a Novel Therapeutic Agent for Targeted Pulmonary Hypertension Therapy. Issue 4 (October 2020) - Wang, Jie; Hu, Li; Huang, Huijie; Yu, Yanfang; Wang, Jingshen; Yu, Youjia; Li, Kai; Li, Yan; Tian, Tian; Chen, Feng
Abstract : In recent years, mesenchymal stem cells (MSCs)–derived extracellular vesicles (EVs) are emerging as a potential therapeutic agent for pulmonary hypertension (PH). However, the full realization of MSCs-derived EVs therapy has been hampered by the absence of standardization in MSCs culture and the challenges of industrial scale-up. The study was to exploit an alternative replacement for MSCs using currently commercialized stem cell lines for effective targeted PH therapy. ReNcell VM—a human neural stem cell line—has been utilized here as a reliable and easily adoptable source of EVs. We first demonstrated that ReNcell-derived EVs (ReNcell-EVs) pretreatment effectively prevented Su/Hx (SU5416/hypoxia)-induced PH in mice. Then for targeted therapy, we conjugated ReNcell-EVs with CAR (CARSKNKDC) peptide (CAR-EVs)—a peptide identified to specifically target hypertensive pulmonary arteries, by bio-orthogonal chemistry. Intravenous administration of CAR-EVs selectively targeted hypertensive pulmonary artery lesions especially pulmonary artery smooth muscle cells. Moreover, compared with unmodified ReNcell-EVs, CAR-EVs treatment significantly improved therapeutic effect in reversing Su/Hx-induced PH in mice. Mechanistically, ReNcell-EVs inhibited hypoxia-induced proliferation, migration, and phenotype switch of pulmonary artery smooth muscle cells, at least in part, via the delivery of its endogenous highly expressed miRNAs, let-7b-5p, miR-92b-3p, and miR-100-5p. In addition, we also found that ReNcell-EVs inhibited hypoxia-induced cell apoptosis and endothelial-mesenchymal transition in human microvascular endothelial cells. Taken together, our results provide an alternative to MSCs-derived EVs–based PH therapy via using ReNcell as a reliable source of EVs. Particularly, our CAR-conjugated EVs may serve as a novel drug carrier that enhances the specificity and efficiency of drug delivery for effective PH-targeted therapy. Abstract : Supplemental Digital Content is available in the text.